Individualist–Collectivist Differences in Climate Change Inaction: The Role of Perceived Intractability - Xiang, Peng; Zhang, Haibo; Geng, Liuna; Zhou, Kexin; Wu, Yuping (Frontiers in Psychology, 2019)
The willingness to take action against climate change may be shaped by cultural orientations. The present study investigated individualist-collectivist differences in climate change inaction as well as the mediating role of perceived intractability. In Study 1, a survey of 182 undergraduates showed that greater perceived intractability of climate change was significantly related to a lower frequency of climate-friendly actions in the preceding six months. In Study 2, participants who were exposed to information concerning the intractability of climate change (experimental group, n = 98) reported a significantly greater perceived intractability of climate change and lower intention to assume a low-carbon lifestyle than those presented with neutral information (control group, n = 83). Based on Studies 1 and 2, participants with collectivist or individualist orientations were recruited from a pool of Chinese undergraduate students in Study 3. We found that participants with a more individualist orientation (n = 62) are more subject to perceived intractability, and less likely to take climate-friendly action than those with a more collectivist orientation (n = 94), and individualist/collectivist status affects climate change inaction through perceived intractability as mediator. The implications of these findings are discussed in relation to the promotion of public engagement with climate change by mitigating perceived intractability.